Adaptação de uma dieta artificial para linhagem e sexagem genética de Anastrepha fraterculus (Diptera: Tephritidae) e doses para indução para esterilidade sob hipóxia - Prestes, Ana Júlia de Carvalho (Universidade Federal de São Carlos, 2024)
The Anastrepha fraterculus fly, also known as the South American fruit fly, is one of the main pests in Brazilian fruit farming. Therefore, the production of sterile males through irradiation (Sterile Insect Technique - SIT) for release in the field is of paramount importance for its biological control. Within this context, to enable the release of only sterile males, it is necessary to develop a strain that allows genetic sexing (Genetic Sexing Strain - GSS) or the elimination of females at some stage of the production process and the biological cycle, which usually occurs in the egg and pupal stages. Thus, a GSS based on the pupal color dimorphism, that is, males emerging from brown pupae and females emerging only from black pupae, has been developed and reared semi-massively. However, before recommending the use of this GSS for large-scale programs integrating SIT, it was necessary to test different artificial diets and determine the ideal sterilizing dose for males, ensuring the maintenance of the strain over generations. Thus, it was observed that the diet based on cornmeal with carrageenan was the most suitable for artificial rearing, and the sterilizing dose required for this strain was approximately 70Gy.
Adaptation of an artificial diet for strain and genetic sexing of Anastrepha fraterculus (Diptera: Tephritidae) and doses for induction of sterility under hypoxia
Keywords: Mosca-das-frutas; Macho estéril; Anastrepha fraterculus; Genetic Sexing Strain; Fruit fly; Sterile male; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE